ROLE OF KIM-1, CYSTATIN C, AND MICROALBUMINURIA AS EARLY MARKERS OF GOUTY NEPHROPATHY IN PATIENTS WITH GOUT - Rakhmatov Avazbek Mamat ugli (Ethiopian International Journal of Multidisciplinary Research, 2026)
Early detection of renal injury in patients with gout remains an important clinical problem, since conventional indicators do not always reflect subclinical kidney damage. Biomarkers such as kidney injury molecule-1 (KIM-1), cystatin C, and microalbuminuria (MAU), together with glomerular filtration rate (GFR), may improve early diagnosis of gouty nephropathy. To assess the diagnostic significance of KIM-1, cystatin C, microalbuminuria, and glomerular filtration rate in the early detection of gouty nephropathy in patients with gout. A total of 186 individuals were included in the study. The control group consisted of 96 healthy subjects. The patient cohort comprised 90 patients with gout and was divided into two groups: Group 1 included 45 patients with gout without gouty nephropathy, and Group 2 included 45 patients with gouty nephropathy. Serum creatinine, cystatin C, urinary KIM-1, microalbuminuria, and GFR were assessed. GFR was estimated using creatinine-based, cystatin C-based, and combined creatinine/cystatin C approaches. Statistical significance was assessed relative to the control group and between the two patient groups. KIM-1, cystatin C, and MAU levels progressively increased from the control group to Group 1 and were highest in Group 2. KIM-1 increased from 0.3 in controls to 1.0 in Group 1 and 2.6 in Group 2. Cystatin C increased from 0.6 to 0.95 and 1.35, respectively. MAU increased from 15 in controls to 28 in Group 1 and 130 in Group 2. Serum creatinine also rose progressively (70, 85, and 119, respectively). In contrast, GFR declined across the groups. Creatinine-based GFR decreased from 114 in controls to 96 in Group 1 and 58 in Group 2. Cystatin C-based GFR declined from 112 to 93 and 52, while combined creatinine/cystatin C GFR decreased from 112 to 93 and 56, respectively. The most pronounced abnormalities were observed in patients with gouty nephropathy. KIM-1, cystatin C, and microalbuminuria are informative early markers of renal injury in patients with gout. Their increase, together with a progressive decline in GFR, reflects the development and progression of gouty nephropathy. Combined assessment of these parameters may improve early diagnosis and risk stratification in patients with gout.